Epidemiological and Clinical Profile of Hemophilia Patients in Libya: A Cross-sectional Study - Adell Abubakeer; HusamUlden Ahmed Hamed; Nasr al-Din Nasiya; Anwar Salm Kalifa Kafo (Libyan Journal of Medical and Applied Sciences, 2025)
Background: Hemophilia is a rare inherited bleeding disorder with significant public health implications. Limited epidemiological data are available on haemophilia in Libya, making evidence-based planning and care. Objective: To characterize hemophilia patients in Libya by examining their epidemiological, challenging clinical, and laboratory features, exploring correlations among demographic and clinical parameters, and providing an overview to improve care and analyze the frequency and patterns of bleeding disorders. Methods: A cross-sectional study was conducted on haemophilia patients in various regions of Libya, focusing on those registered with the Libyan Association for Hemophilia. Data were collected through structured questionnaires and laboratory records, covering demographics, haemophilia types, severity, coagulation deficiencies, antibody presence, bleeding patterns, family history, comorbidities, and treatment practices. Statistical analysis included descriptive statistics and chi-square tests, with significance set at p < 0.05. Results: A total of 230 patients were included. Most cases were concentrated in Tripoli (36.1%), followed by Zliten (8.3%), Benghazi (7%), and Al Khoms (5.2%). Haemophilia A was the most common type (67.8%), followed by haemophilia B (10.9%), von Willebrand disease (9.6%), and haemophilia C (3%). Factor VIII deficiency predominated (68.3%). Moderate severity was most frequent (50%), followed by severe (37%) and mild (13.5%) cases. Most patients were antibody-negative (80%). Joint bleeding was the most frequent site (36.5%). Kinship between parents was reported in 49.1% of cases, and 66.5% of participants reported relatives with haemophilia. Conclusion: This study highlights the predominance of haemophilia A and factor VIII deficiency in Libya, with a high proportion of moderate-to-severe cases. Joint bleeding remains the most frequent clinical complication, and consanguinity plays a considerable role in disease occurrence. Early diagnosis and targeted prevention strategies are needed to improve patient outcomes.